On Solvability of the Boundary Value Problems for the Multidimensional Elliptic Systems of Partial Equations - Paliokas, E. (Nonlinear Analysis: Modelling and Control, 2002)
The investigation of a question of solvability boundary value problems for elliptic partial systems is presented. Attention is paid to differences in case of two independent variables and of multidimensional one.
Keywords: boundary value problem; elliptic partial system; solvability